2018
DOI: 10.1016/j.mri.2017.12.011
|View full text |Cite
|
Sign up to set email alerts
|

Pseudo continuous arterial spin labeling quantification in anemic subjects with hyperemic cerebral blood flow

Abstract: Purpose To investigate possible sources of quantification errors in global cerebral blood flow (CBF) measurements by comparing pseudo continuous arterial spin labeling (PCASL) and phase contrast (PC) MRI in anemic, hyperemic subjects. Methods All studies were performed on a Philips 3T Achieva MRI scanner. PC and PCASL CBF examinations were performed in 10 healthy, young adult subjects and 18 young adults with chronic anemia syndromes including sickle cell disease and thalassemia. CBF estimates from single an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
33
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 30 publications
(35 citation statements)
references
References 51 publications
2
33
0
Order By: Relevance
“…Such a disconnect between global and local oxygen delivery is commonly observed in arteriovenous malformations, but recent work suggests that functional arteriovenous shunting also occurs in patients with chronic anemia syndromes, including SCD. [6][7][8] Our work using MRI oximetry of sagittal sinus blood also supports the functional shunting hypothesis. We found that children and young adults with SCD (particularly children receiving chronic transfusion therapy) exhibited inappropriately low whole-brain OEF for their degree of anemia and CBF.…”
supporting
confidence: 69%
See 2 more Smart Citations
“…Such a disconnect between global and local oxygen delivery is commonly observed in arteriovenous malformations, but recent work suggests that functional arteriovenous shunting also occurs in patients with chronic anemia syndromes, including SCD. [6][7][8] Our work using MRI oximetry of sagittal sinus blood also supports the functional shunting hypothesis. We found that children and young adults with SCD (particularly children receiving chronic transfusion therapy) exhibited inappropriately low whole-brain OEF for their degree of anemia and CBF.…”
supporting
confidence: 69%
“…Interestingly, misty and moonlight hypopigmentation mice are both the result of mutations in Dock7 that cause truncations either inside (misty) or downstream (moonlight) of DHR-1. 5,6 Although these animals have been studied for their defects in neurogenesis, misty mice have a bleeding diathesis, which mimics the NBEAL2 2/2 phenotype. 6 Moonlight mice do not have that phenotype.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Lower cerebral vascular reserve predicts white matter hyperintensities cross‐sectionally and longitudinally, presumably through acute‐on‐chronic interruptions in oxygen delivery . Additionally, low extraction reserve has been found in patients with high cerebral blood flow . This is possibly attributed to decreased diffusion time, capillary transit time heterogeneity, and/or artereo‐vascular shunting in capillary beds .…”
Section: Discussionmentioning
confidence: 99%
“…However, it assumes that longitudinal relaxation rates are identical across tissue types, making it unsuitable for accurate WM CBF estimation [15]. Therefore, we used a modified two compartment kinetic quantification model proposed by Wang et.…”
Section: Methodsmentioning
confidence: 99%